Respuesta :
2x - 10 = 10 - 3x
Simplifying
2x + -10 = 10 + -3x
Reorder the terms:
-10 + 2x = 10 + -3x
Solving
-10 + 2x = 10 + -3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation.
-10 + 2x + 3x = 10 + -3x + 3x
Combine like terms: 2x + 3x = 5x
-10 + 5x = 10 + -3x + 3x
Combine like terms: -3x + 3x = 0
-10 + 5x = 10 + 0
-10 + 5x = 10
Add '10' to each side of the equation.
-10 + 10 + 5x = 10 + 10
Combine like terms: -10 + 10 = 0
0 + 5x = 10 + 10
5x = 10 + 10
Combine like terms: 10 + 10 = 20
5x = 20
Divide each side by '5'.
x = 4
Simplifying
x = 4
Answer:
X=9
Step-by-step explanation:
10(3x-8)-40=150
10(3x-8)-40+40=150+40
10(3x-8)=190
Next you would divide the 10(3x-8) over 10 and 190 over 10
3x-8=19
3x-8+8=19+8
3x=27
Divide those both by 3
x=9